Exploration of the Antioxidant and Anti-inflammatory Potential of Cassia sieberiana DC and Piliostigma thonningii (Schumach.) Milne-Redh, Traditionally Used in the Treatment of Hepatitis in the Hauts-Bassins Region of Burkina Faso - Eliasse Zongo; Anna Busuioc; Roland Nâg-Tiero Meda; Andreea Veronica Botezatu; Maria Daniela Mihaila; Ana-Maria Mocanu; Sorin Marius Avramescu; Benjamin Kouliga Koama; Sami Eric Kam; Hadidiatou Belem; Franck Le Sage Somda; Clarisse Ouedraogo; et al. (MDPI AG, 2023)
Inflammation is the supreme biological response to illness. In the Hauts-Bassins region, in traditional medicine, all parts of Cassia sieberiana and Piliostigma thonningii are used to treat hepatitis and inflammation. The aim of this study was to evaluate the in vitro antioxidant and anti-inflammatory activities of their aqueous extracts. High performance liquid chromatography with photodiode array (HPLC-DAD) and ultra-high-performance liquid chromatography coupled with high-resolution mass spectrometry (UHPLC-MS/MS) analyses highlighted the presence of polyphenols and flavonoids. Antioxidant and anti-inflammatory activities were measured by various methods such as DPPH (2,2-diphenyl-1-picrylhydrazyl), ABTS 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), TAC (total antioxidant capacity), anti-protease, anti-lipoxygenase, and membrane stabilization. The best antioxidant activity was observed in the bark (DPPH: IC50 = 13.45 ± 0.10 µg/mL) and roots (TAC = 29.68 ± 1.48 mg AAE/g DW) of Piliostigma thonningii and in the roots (ABTS: IC50 = 1.83 ± 0.34 µg/mL) of Cassia sieberiana. The best anti-inflammatory activity was observed in the bark (anti-lipoxygenase: IC50 = 13.04 ± 1.99 µg/mL) and leaves (anti-proteases: IC50 = 75.74 ± 1.07 µg/mL, membrane stabilization: IC50 = 48.32 ± 6.39 µg/mL) of Cassia sieberiana. Total polyphenols (ABTS: r = −0.679, TAC: r = 0.960) and condensed tannins (ABTS: r = −0.702, TAC: r = 0.701) were strongly correlated with antioxidant activity. Total flavonoids (anti-proteases: r = −0.729), condensed tannins (anti-proteases: r = 0.698), and vitamin C (anti-proteases: r = −0.953) were strongly correlated with anti-inflammatory activity. Total polyphenols, flavonoids, condensed tannins, and vitamin C could contribute to the antioxidant and anti-inflammatory activities of the two studied plants. These results could validate the traditional use of these plants to treat various inflammatory diseases.